2016
DOI: 10.1123/ijspp.2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal, Physiological, and Physical Performance During Simulated Kickboxing Combat: Differences Between Winners and Losers

Abstract: The aim of the current study was to investigate the hormonal, physiological, and physical responses of simulated kickboxing competition and evaluate if there was a difference between winners and losers. Twenty athletes of regional and national level participated in the study (mean ± SD age 21.3 ± 2.7 y, height 170.0 ± 5.0 cm). Hormone (cortisol, testosterone, growth hormone), blood lactate [La], and glucose concentrations, as well as upper-body Wingate test and countermovement-jump (CMJ) performances, were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 25 publications
5
36
1
4
Order By: Relevance
“…These variables have been reported for both upper and lower-body actions in kickboxers [8, 12, 13, 20–22]. The available studies showed that mean power output values for upper and lower body of male amateur kickboxers were about 3.2 ± 0.7 W ∙ kg -1 and 6.7 ± 1 W ∙ kg -1 , respectively [13].…”
Section: Discussionmentioning
confidence: 92%
“…These variables have been reported for both upper and lower-body actions in kickboxers [8, 12, 13, 20–22]. The available studies showed that mean power output values for upper and lower body of male amateur kickboxers were about 3.2 ± 0.7 W ∙ kg -1 and 6.7 ± 1 W ∙ kg -1 , respectively [13].…”
Section: Discussionmentioning
confidence: 92%
“…Ist nie ją sprzeczne do nie sie nia od no śnie do związ ku po mię dzy hor monal nym sta tu sem a za le żnym od dys cy pli ny wy ni kiem spor to wym, na wet w cza sie za wo dów o po dob nej struktu rze za da nia. Dla przy kła du, w kick -bo xingu hor monal ny sta tus nie ró żni cu je zwy cię ża ją cych i prze grywa ją cych spor tow ców [2], pod czas gdy wśród in nych spor tów walk [3,4] i ma ra toń czy ków [5] po ziom C i T był wy ższy u zwy cięz ców. Nie któ re ba da nia sku pia ją się na za le żnych od płci ró żni cach w re ak cjach hormo nal nych na za wo dy.…”
Section: Wstępunclassified
“…There are conflicting reports about the connection between hormonal status and sport-related outcomes, even during competitions of similar task structures. For example, in kick-boxing hormonal status did not differentiate winners and losers [2], while in the other combat sports [3,4] and marathon runners [5], winning athletes did display higher plasma C and T. Some studies focused on gender differences in the hormonal responses to a competition. Contradictory results were reported depending the sporting discipline.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the testosterone/cortisol ( T/C ) ratio has been considered as an accurate indicator of overtraining in athletes [ 22 ]. Accordingly, several studies have reported that striking combat sports competition is a very high intensity and stressful activity that results in increased C levels [ 5 , 16 , 24 ]. In contrast, the same consensus does not apply to karate kata and kumite due to significant increases in glucose, T and catecholamines levels, without significant changes in insulin and C concentrations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%